Probability and random variables - Beaumont, G. P. (Geoffrey P.) (Ellis Horwood series in mathematics and its applications. Statistics and operational research., 2005)
This undergraduate text distils the wisdom of an experienced teacher and yields, to the mutual advantage of students and their instructors, a sound and stimulating introduction to probability theory. The accent is on its essential role in statistical theory and practice, built on the use of illustrative examples and the solution of problems from typical examination papers. Mathematically-friendly for first and second year undergraduate students, the book is also a reference source for workers in a wide range of disciplines who are aware that even the simpler aspects of probability theory are not simple. Provides a sound and stimulating introduction to probability theoryPlaces emphasis on the role of probability theory in statistical theory and practice, built on the use of illustrative examples and the solution of problems from typical examination papers.